The molecular structure of spider dragline silk: Folding and orientation of the protein backbone - van Beek, J. D. (National Academy of Sciences, 2002)
The design principles of spider dragline silk, nature's high-performance fiber, are still largely unknown, in particular for the noncrystalline glycine-rich domains, which form the bulk of the material. Here we apply two-dimensional solid-state NMR to determine the distribution of the backbone torsion angles (φ,ψ) as well as the orientation of the polypeptide backbone toward the fiber at both the glycine and alanine residues. Instead of an “amorphous matrix,” suggested earlier for the glycine-rich domains, these new data indicate that all domains in dragline silk have a preferred secondary structure and are strongly oriented, with the chains predominantly parallel to the fiber. As proposed previously, the alanine residues are predominantly found in a β sheet conformation. The glycine residues are partly incorporated into the β sheets and otherwise form helical structures with an approximate 3-fold symmetry.